RNA interference inhibits yellow fever virus replication in vitro and in vivo - Pacca, Carolina C. [UNESP]; Severino, Adriana A. [UNESP]; Mondini, Adriano; Rahal, Paula [UNESP]; D'avila, Solange G. P.; Cordeiro, Jose Antonio; Lelles Nogueira, Mara Correa; Bronzoni, Roberta V. M.; Nogueira, Mauricio L. (Springer, 2009)
RNA interference (RNAi) is a process that is induced by double stranded RNA and involves the degradation of specific sequences of mRNA in the cytoplasm of the eukaryotic cells. It has been used as an antiviral tool against many viruses, including flaviviruses. The genus Flavivirus contains the most important arboviruses in the world, i.e., dengue (DENV) and yellow fever (YFV). In our study, we investigated the in vitro and in vivo effect of RNAi against YFV. Using stable cell lines that expressed RNAi against YFV, the cell lines were able to inhibit as much as 97% of the viral replication. Two constructions (one against NS1 and the other against E region of YFV genome) were able to protect the adult Balb/c mice against YFV challenge. The histopathologic analysis demonstrated an important protection of the central nervous system by RNAi after 10 days of viral challenge. Our data suggests that RNAi is a potential viable therapeutic weapon against yellow fever.
Keywords: RNAi; Yellow fever; Flaviviridae; Arboviruses